2020
DOI: 10.1177/0145561320938918
|View full text |Cite
|
Sign up to set email alerts
|

Is It Important Which Suturing Technique Used for Pharyngeal Mucosal Closure in Total Laryngectomy? Modified Continuous Connell Suture May Decrease Pharyngocutaneous Fistula

Abstract: Objective: The aim of this study is to research the correlation between pharyngeal mucosal suture techniques and pharyngocutaneous fistula (PCF) development after total laryngectomy. We also aimed to investigate other risk factor for fistula development. Methods: Medical charts of 85 patients who had total laryngectomy during August 2016 and February 2020 were reviewed. Sixteen patients were excluded due to exclusion criteria. Patients were grouped according to pharyngeal mucosal suture technique. Group 1 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A study based on the Japanese national inpatient database reported 20 days as the median for oral feeding after pharyngolaryngectomy for HPC patients without PCF. Some institutions do not do any test before restarting oral intake, 16,21 while others perform a methylene blue test first. 22 Based on the findings of this study, a swallow X-ray is ideal before initiation of oral intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study based on the Japanese national inpatient database reported 20 days as the median for oral feeding after pharyngolaryngectomy for HPC patients without PCF. Some institutions do not do any test before restarting oral intake, 16,21 while others perform a methylene blue test first. 22 Based on the findings of this study, a swallow X-ray is ideal before initiation of oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there should be no tension on the first suture line. Though a modified continuous Connell suture significantly reduces PCF incidence to 16% after total laryngectomy (TL), 16 it was not preferred because it is time-consuming and inverts mucosal edges, which hinders mucosal healing. Herein, the MLFU technique in ALT reconstruction was especially useful because it significantly reduced PCF incidence for salvage cases to 3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found out that interrupted suturing technique is better as each individual stitch provide strength to the wall of neopharynx separately as compared to the continuous suturing technique in which a single thread is used to stitch the first layer of neopharynx through and through. As a single thread is involved in stitching in the second method it has more chances of loosening also if it gets open up at one point the entire layer can get open and hence increase chances of pharyngocutaneous fistula formation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, interrupted sutures provide better security. Recent studies have shown that the use of continuous sutures is associated with lower fistula rates than interrupted sutures in mucosal repair [67,72,73].…”
Section: The Mucosal Layermentioning
confidence: 99%